Hypermedia Interaction Design : A Cognitive Constructivist Approach - Lee , Chien Sing (2005)
E-Learning serves as a means to implement models within various teaching and learning modes (such as face-to-face, on-line, Web-based or mobile) based on electic applications of educational theories such as behaviourism, cognitivism and constructivism. Two key problems often cited are disorientation and cognitive overload. A possible solution is to improve the usability of hypermedia by personalising domain knowledge to the students' need as found in adaptive hypermedia learning systems.